CHARACTERISTICS OF SKILLS AND SKILLS OF SELF-CONTROL AND STAGES OF THEIR FORMATION IN STUDENTS IN THE PROCESS TEACHING - Seryogina, I.Yu. (Pedagogy of Higher and Secondary Education, 2008)
In the article author analyses the notion of abilities and skills of self-control, defines the stages of its forming at the pupils in the process of their educational-cognitive activity.